Libya and Turkey’s expansion policy in Africa - Bagci, Hüseyin (2017)
This article analyzes Turkey’s need to make increased efforts to ameliorate relations with Libya in order to successfully advance the “African Evolution” initiatives. The study covers the AKP period since 2009, including the rebellion conducted by the Benghazi rebels up to the death of Gaddafi and the post-Gaddafi period up to now.